Integrating Kaizen Culture and Occupational Safety and Health in Enhancing Employee Productivity: A Study in the Precision Manufacturing Industry - Muhamad Baharudin; Fibi Eko Putra; Wahyu Hadikristanto (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The precision component manufacturing industry faces a dual challenge in enhancing productivity while maintaining occupational safety, given that production processes involve machinery and high-risk activities. This study aims to analyze the effect of implementing kaizen culture and Occupational Safety and Health (OSH) on employee productivity, both partially and simultaneously, within the F-Line Department of PT XYZ Indonesia, a manufacturer of spinnerettes for the synthetic fiber industry. A quantitative approach with an explanatory design was applied to 64 respondents selected through saturated sampling technique. Data were collected using a five-point Likert-scale questionnaire, transformed into interval scale data using the Method of Successive Interval (MSI), and subsequently analyzed using multiple linear regression with the assistance of SPSS version 25.0, following validity, reliability, and classical assumption tests—including normality, multicollinearity, and heteroscedasticity. The results indicate that kaizen culture has a positive and significant effect on employee productivity (t = 6.456; p = 0.000), as does OSH (t = 4.642; p = 0.000). Simultaneous testing reveals that both variables significantly affect employee productivity (F = 214.236; p = 0.000), with a coefficient of determination (R2) of 0.875, indicating that 87.5% of the variation in employee productivity is explained by these two variables. Kaizen culture demonstrates a relatively more dominant contribution than OSH. These findings suggest that kaizen culture and OSH are complementary in supporting operational performance. Accordingly, precision manufacturing companies are advised to integrate both programs synergistically—rather than as standalone initiatives—to optimize employee productivity while continuously mitigating the risk of workplace accidents.